A Micro Polymerase Chain Reaction Module for Integrated and Portable DNA Analysis Systems. (15th March 2011) - Morganti, Elisa; Collini, Cristian; Potrich, Cristina; Ress, Cristina; Adami, Andrea; Lorenzelli, Leandro; Pederzolli, Cecilia
Abstract : This work deals with the design, fabrication, and thermal characterization of a disposable miniaturized Polymerase Chain Reaction (PCR) module that will be integrated in a portable and fast DNA analysis system. It is composed of two independent parts: a silicon substrate with embedded heater and thermometers and a PDMS (PolyDiMethylSiloxane) chamber reactor as disposable element; the contact between the two parts is assured by a mechanical clamping obtained using a Plastic Leaded Chip Carrier (PLCC). This PLCC is also useful, avoid the PCR mix evaporation during the thermal cycles. Finite Element Analysis was used to evaluate the thermal requirements of the device. The thermal behaviour of the device was characterized revealing that the temperature can be controlled with a precision of ±0.5°C. Different concentrations of carbon nanopowder were mixed to the PDMS curing agent in order to increase the PDMS thermal conductivity and so the temperature control accuracy.